What is masculinity? historical dynamics from antiquity to the contemporary world - Arnold, John 1969-; Brady, Sean 1964- (Genders and sexualities in history., 2013)
What is masculinity? Looked at across time - from antiquity to the modern day the contours of 'manliness' take on an intriguing complexity. As the various contributors to this volume demonstrate, the ideas and practices of male identity have varied considerably over time and place: masculinity proves to be a slippery concept, one not available to all men, and one sometimes even applied to certain women. This ground-breaking book presents a variety of new perspectives on the nature of masculinity, its social and political functions, and the methods by which historians and others might seek to analyse it. Each author provides both a case study of what masculinity means (or fails to mean) in a specific historical moment, and contributes to a wider collective analysis of the changing historical dynamics to male identity. Overall, the book provides a key methodological landmark in the study of gender history.